Chatbot Based on Clinical Literature for Decision Support - Sánchez Montejo, Irene; Trillo Lado, Raquel; Telleria Oriols, Carlos (Jornada de Jóvenes Investigadores del I3A, 2023)
We provide a thesis approach to evaluate different language models which are able to analyze documents to extract the essential information from each one, and develop a chatbot capable of answering according to clinical practice guidelines and biomedical literature, which provides the latest in diagnostic and treatment for each disease.